The Bones of the System: A Study of Logging and Telemetry at Microsoft - Barik, Titus; DeLIne, Robert; Drucker, Steven; Fisher, Danyel (ICSE '16 Proceedings of the 38th International Conference on Software Engineering Companion, 2016)
Large software organizations are transitioning to event data platforms as they culturally shift to better support data-driven decision making. This paper offers a case study at Microsoft during such a transition. Through qualitative interviews of 28 participants, and a quantitative survey of 1,823 respondents, we catalog a diverse set of activities that leverage event data sources, identify challenges in conducting these activities, and describe tensions that emerge in data-driven cultures as event data flow through these activities within the organization. We find that the use of event data span every job role in our interviews and survey, that different perspectives on event data create tensions between roles or teams, and that professionals report social and technical challenges across activities.